Polypoid Endometriosis in A Postmenopausal Woman Treated With Tamoxifen Due to DCIS: A Case Report And Review of the Literature - Roxana, Schwab; Ioannis, Boutas; Evelyn, Dappa; Elke, Kohlwes; Michaela, Bossart; Joerg, Woll; Anastasios, Potiris; Klaudija, Künzel; Annette, Hasenburg (Archives of Clinical and Biomedical Research, 2020)
Patient: We present a case of polypoid endometriosis in a postmenopausal 58 years old patient presenting with a pelvic retroperitoneal nodule mimicking a neoplasm. Additionally, the patient reported uterine bleeding three years after starting tamoxifen for ductal carcinoma in situ (DCIS) of the breast. Preoperative magnetic resonance imaging suggested the nodule as an endometriotic lesion. Interventions: Imaging results described a combined solid and liquid adnexal mass close to the right ovary. At laparoscopy, a 5-centimeter large parauterine retroperitoneal mass was identified medial to the right ureter. The suspected mass was completely resected and a subsequent hysterectomy was performed because of recurrent postmenopausal bleeding. Main outcome measures: Exclusion of malignancy (and resolution of postmenopausal bleeding). Results: Pathologic diagnosis revealed polypoid endometriosis and a uterine polyp. Conclusion: Polypoid endometriosis is a very rare disease but should be taken into account in postmenopausal women with use of tamoxifen or hormonal therapy. This case emphasizes the importance of broad differential diagnosis for an adnexal mass in the menopause. To our knowledge this is the first case of polypoid endometriosis in a postmenopausal woman treated with Tamoxifen for DCIS.